PENGARUH KEPUASAN KERJA DAN MOTIVASI KERJA TERHADAP KINERJA DOSEN FAKULTAS EKONOMI DI PERGURUAN TINGGI SWASTA DI MAKASSAR - Bandhaso, Mira Labi; Paranoan, Natalia (Jurnal Akun Nabelo: Jurnal Akuntansi Netral, Akuntabel, Objektif, 2019)
This study aims to determine the effect of job satisfaction and motivation on the lecturer performance at private universities in Makassar. The research conducted on the lecturer of faculty of economics at three private universities in Makassar South Sulawesi by using mail survey and sending 150 questionnaires to the respondents. Sampling technique used in this study is random sampling. Data were collected at 101 and analyzed using multiple linear regression analysis. The analysis result showed that job satisfaction gives positive impact and significant on the performance of private university lecturers in Makassar, and motivation gives positive impact and significant on the performance of private university lecturers in Makassar. The results of multiple regression analysis showed motivation and job satisfaction simultaneously have positive and significant impact on the performance of private university lecturers in Makassar.